The influence of ultrasonic treatment on the solubility of aqueous electrolyte mixtures - Nazarbek Ulzhalgas; Nazarbekova Saule; Kambarova Galiya; Raiymbekov Yerkebulan (E3S Web of Conferences)
This study investigates the influence of ultrasonic treatment on the solubility of aqueous electrolyte mixtures. The aim of the research was to examine the mechanisms of electrolyte solubility enhancement through the use of ultrasonic waves and to determine the optimal process conditions. Saturated solutions of NaCl – H2O and K2SO4 – H2O, prepared using distilled water, were used for the experiments. The results demonstrated that ultrasonic treatment increases the solubility of electrolytes. The most significant effect was observed when salts were dissolved directly during ultrasonic exposure, which is attributed to cavitation processes that intensify mass transfer. It was also found that the preliminary ultrasonic treatment of distilled water alters the structure of the solvent, thereby improving the solubility of salts. The morphological analysis of crystals showed that ultrasonic treatment affects their size and shape, contributing to a more uniform distribution of particles.